1995
DOI: 10.1029/95gl00010
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure of the midlatitude temperature from stratosphere to mesopause (30–105 km)

Abstract: Data sets from Rayleigh lidar (1979–93) at the Observatory of Haute‐Provence (44°N, 6°E) and at Biscarrosse (44°N, 1°W) of southern France, and from narrowband Na lidar (1991–4) at Fort Collins, Colorado (41°N, 105°W) are used to deduce the vertical temperature structure of the midlatitude middle atmosphere from 30–105 km. Nightly averaged temperatures measured across the Atlantic at comparable latitudes between 81 and 90 km showed seasonal variations tracking one another. Harmonic analyses of the measured pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 10 publications
(1 reference statement)
7
28
2
Order By: Relevance
“…It is broad (∼7 km) in the month of April and September. She et al (1993), Senft et al (1994), using Sodium lidar temperature observations reported, that for the seasons where the inversion layer was observed in average temperature data, the layer width of about 5 km is seen and the amplitude of the layer is typically 5 to 10 K. However, the results of the above two authors pertain to mid-latitude, whereas the results of the present study relate to equatorial and the low mid-latitude region (0-30 • N). The characteristics and causes of mesospheric inversion could be different in the two regions.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…It is broad (∼7 km) in the month of April and September. She et al (1993), Senft et al (1994), using Sodium lidar temperature observations reported, that for the seasons where the inversion layer was observed in average temperature data, the layer width of about 5 km is seen and the amplitude of the layer is typically 5 to 10 K. However, the results of the above two authors pertain to mid-latitude, whereas the results of the present study relate to equatorial and the low mid-latitude region (0-30 • N). The characteristics and causes of mesospheric inversion could be different in the two regions.…”
Section: Resultscontrasting
confidence: 55%
“…A number of later studies using different techniques viz. Rayleigh lidar (Hauchecorne et al, 1987;Jenkins et al, 1987;Meriwether et al, 1998;Thomas et al, 2001;Kumar et al, 2001), Sodium temperature lidar (States and Gardner, 1998;Chen et al, 2000;She et al, 1995), satellite photometry (Leblanc and Hauchecorne, Correspondence to: S. Fadnavis (suvarna@tropmet.res.in) 1997; Clancy et al, 1989Clancy et al, , 1994, etc., have repeatedly detected this mesospheric inversion layer phenomenon. Whiteway et al (1995) reported that inversion layers are associated with an overlying, nearly adiabatic laps rate, which is an indication of a well mixed turbulent layer that is confirmed by a one-dimensional numerical model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, absolute pressure-altitude is registered at around 35 km in the LTE Tk retrieval (i.e., p o = p(z=35 km)) (Remsberg et al, 2004). Many years of lidar measurements at mid-latitudes have been analyzed to deduce the MLT thermal structure (She et al, 1993(She et al, , 1995. The summer (or low) mesopause altitude derived from the lidar analysis is 86 ± 3 km.…”
Section: Temperature Comparisonsmentioning
confidence: 99%
“…These waves are generated at tropospheric altitudes because of effects such as the passage of fronts over intense pressure regions. The waves propagate upwards and grow in amplitude, until reaching a critical level near the mesopause, they "break" depositing energy and momentum [14]. The study of such phenomena is one of the scientific goals of the Odin temperature channels.…”
Section: Introductionmentioning
confidence: 99%